Teaching Language and World Vision: As a Cross-Cultural Communication - Lilis Rahmawati (EDUCATIO : Journal of Education, 2018)
A language contains an implicit classification experience. The language system as a whole contains a vision of the world which by its speakers receipt and projected into reality. Language does not make speakers blind to the facts of the real world, but instead indicate the existence of relationships. Culture is actually an integral part and the interaction of language and mind. Cultural patterns, customs and way of life are expressed in the language, and culture-specific worldviews reflected in its language